'The Gifts and the Calling of God Are Irrevocable' (Rom 11:29): A Theological Reflection. (February 2018) - Moyaert, Marianne
In 2015 the Commission for Religions Relations with the Jews published a document called 'The Gifts and the Calling of God Are Irrevocable' (Rom 11:29 ): A Reflection on Theological Questions Pertaining to Catholic–Jewish Relations on the Occasion of the 50th Anniversary of 'Nostra Aetate' (no. 4). In this article I will focus in particular on some of the theological questions that are addressed in sections 3 through 6—questions that have increasingly moved into the foreground in the dialogue in recent decades. In particular, I will explore the relation between the old and new covenant, how the uniqueness and universality of salvation in Christ are related to the recognition that God's covenant with Israel has never been revoked, and the question of the mission to the Jews. In presenting the document and grappling with it, (1) I will glance back briefly and outline the theological status quaestionis, I will then (2) analyze what new developments The Gifts formulates. Finally, moving beyond the document, (3) I will engage it in discussion.